Edukacyjny aspekt uczestnictwa dzieci i studentów w zajęciach umuzykalniających = The educational aspect of the participation of children and students in the musical activity - Kataryńczuk-Mania, Lidia (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
The article presents the aims and tasks of the musical classes conducted in kindergarten. The possibility of performing various artistic forms and practical examples during the joint musical activities of children and students was presented.
Keywords: zajęcia umuzykalniające; aktywność muzyczna dzieci; praktyka studentów; music classes; children`s musical activity; students practice